Políticas públicas educacionais na Penitenciária Estadual de Maringá - Paraná (1999-2010): possibilidade de reinserção social do apenado - Garutti, Selson (2015)
The present thesis is linked to the Program of Post-Graduation in Education, Concentration area: History and Education Policy. Entitled " Public Educational Policies in the State Penitentiary of Maringa-Paraná (1999-2010): possibility of social rehabilitation of the inmates.", analyzes educational policies for the prison system that have been implemented at the State Penitentiary in Maringa, Parana (PEM-PR) from the political cycle on Public Security, consisting of its subsystems, in its implications and contributions to the process of social reintegration for inmates. The complex Penitentiary System (Paraná) was going through a deep crisis of legitimacy of their innocuous actions, coming in recent decades, the state delegate responsibilities of goods and services to the private sector, thus, different management models, characterized by the participation of society civil. With this, we can see a paradigm shift in state action, direct provider to regulator, with immediate repercussions for the substance of Educational Public Policy for the Prison System in Paraná as a whole. Also, the Brazilian prison system, as a political institution, still maintains a punitive, rather than an educational, social reintegration of inmates, ie, there is a clear contradiction between what is constituted in the legal system and what is effectively held in the prison system, preventing thus the implementation of public policies that actually produce results. From these contradictions, this research aims to analyze the educational activities implemented in the Maringa State Penitentiary - Paraná, between the years 1999 to 2010 as a public policy as a possibility of social rehabilitation of inmates. Qualitative research, documentary and field whose theoretical framework the Policy Cycles Model, consisting of Howlett; Ramesh; Perl (2013). With respect to the structure of the thesis, the text is divided into a total of three chapters. In the first chapter the historical context in which renders this research, therefore, constitutes a bibliographical review of the documentation produced by the State concerning public safety in its various classifications. In the second chapter, the contextualization of the field of policies, critical to the analysis of public policies, emphasizes the conceptual aspects of the analytical model of the Political cycle, as a mechanism for understanding the process of policy formulation. In the third chapter are presented the results of documentary research in the area of Occupational and qualification Division of State Penitentiary from Maringa (DIOQ-PEM-PR) and field research in the space the CEEBJA "Teacher Tomires Moreira de Carvalho" (School allocated within the PEM), having as a tool for collecting a semi-structured questionnaire, applied to the subject of the search. As well as the analysis of data collected in the survey about educational actions implemented in PEM during the period delimited. These results support the conclusion that, in the period studied, educational Public Policies implemented in the Maringa State Penitentiary were classified as type of distributive policy, benefiting a large number of recipients, but in relatively small scale. Aimed distribute individual benefits, exploited by clientelism, there were many different interests and access opportunities, which reduced the chances of conflict. Therefore, served very well as redemptive mechanism to reduce the prison population and not as an emancipatory public policy of the subjects inmates in conditions of social vulnerability